Postmodernism and philosophical deconstruction. What is the difference? - Kwietniewska, Małgorzata (Hybris, 2022)
The subject of this article is a comparison between postmodern philosophy and philosophy of difference, especially in its most recent version, which is philosophical deconstruction. In the first part of the paper, the history and general characteristics of postmodernism are briefly presented, while the second part discusses the philosophy of difference, not only in its present form, but also in its earlier versions, which include Martin Heidegger's “different thinking”, German idealism, Presocratic thought, and finally the philosophy of ancient India. Unlike the postmodernists, who are ultimately united almost exclusively by their critique of metaphysics and their literary style of discourse, the theorists of difference remain representatives of a traditional (though now largely forgotten) understanding of philosophy.